Modeling of chronic epilepsy in animals through chemical methods - E. V. Egorova; D. V. Dmitrenko; A. A. Usoltseva; A. M. Iptyshev; N. A. Shnayder; R. F. Nasyrova (Бюллетень сибирской медицины)
According to the World Health Organization, the prevalence of epilepsy in the world is high, at about 0.5–1% of the world’s population. In 20–40% of cases, according to various sources, it is not possible with standard treatment methods to achieve control over attacks, which significantly impairs the patient’s quality of life, increases economic costs, and poses a difficult task for the doctor to select the optimal treatment to reduce the frequency of attacks. This explains the urgency of creating new and modifying classical antiepileptic drugs (AEDs), as well as finding optimal and safe ways of administering and delivering the drugs. To study the mechanisms of AEDs’ effect on various pathways of epileptogenesis, simulation of convulsive seizures and chronic epilepsy in animals is used; for this purpose, mechanical, physical, chemical, and genetic models of epilepsy are used. The present review discusses chemical models of chronic epilepsy, which are most often used in experimental neuroscience today. It also describes the characteristics, advantages and disadvantages of each of them, the specificity of the study where they can be used and the assessment scales for epileptic seizures in animals.